Effect of bovine amniotic fluid on intra abdominal adhesions - Durmus, A. S.; Han, M. C. (Indian Veterinary Journal, 2006)
[Abstract Not Available]
Keywords: Intraabdominal Adhesions; Plasminogen-Activator; Hyaluronic-Acid; Prosthetic Mesh; Prevention; Surgery